2014
DOI: 10.1145/2601097.2601137
|View full text |Cite
|
Sign up to set email alerts
|

Style transfer for headshot portraits

Abstract: Headshot portraits are a popular subject in photography but to achieve a compelling visual style requires advanced skills that a casual photographer will not have. Further, algorithms that automate or assist the stylization of generic photographs do not perform well on headshots due to the feature-specific, local retouching that a professional photographer typically applies to generate such portraits. We introduce a technique to transfer the style of an example headshot photo onto a new one. This can allow one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
200
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(201 citation statements)
references
References 44 publications
1
200
0
Order By: Relevance
“…Model-based methods detect motions by comparing the target with a built model. It is ideal to directly use the background image 22 without interference as the model if the scenario is static, but more often, using an estimated model from a priori knowledge is more actual, e.g., Gaussian mixture model (GMM) 23 is proposed for dynamic model estimation according to the Gaussian mixture distribution of pixels, which is widely applied for object tracking. In a very recent work, Haines and Xiang 24 further used a Dirichlet process GMM to provide a per-pixel density estimate for background computation.…”
Section: Motion Detectionmentioning
confidence: 99%
“…Model-based methods detect motions by comparing the target with a built model. It is ideal to directly use the background image 22 without interference as the model if the scenario is static, but more often, using an estimated model from a priori knowledge is more actual, e.g., Gaussian mixture model (GMM) 23 is proposed for dynamic model estimation according to the Gaussian mixture distribution of pixels, which is widely applied for object tracking. In a very recent work, Haines and Xiang 24 further used a Dirichlet process GMM to provide a per-pixel density estimate for background computation.…”
Section: Motion Detectionmentioning
confidence: 99%
“…The algorithm outputs an image whose style matches that of the example image. Shih et al [2014] spatially matches a casual portrait to a target example automatically found in a database; at its core, this technique relies on computationally expensive dense correspondence. Because of correspondence estimation and database dependence, this algorithm is a good candidate for cloud processing.…”
Section: Photo Editing and Photoshop Actionsmentioning
confidence: 99%
“…This includes content-aware photo enhancement [Kaufman et al 2012], dehazing [Kim et al 2013], edge-preserving enhancements Farbman et al 2008], colorization [Levin et al 2004], style transfer [Shih et al 2014;Aubry et al 2014], time-of-day hallucination [Shih et al 2013] but excludes dramatic changes such as inpainting. For this class of enhancements, the input and output images are usually highly correlated.…”
Section: Introductionmentioning
confidence: 99%
“…For this, we establish correspondences among silhouettes and other relevant edges visible in both O, and in P o -the perspective projection image of P as seen from the same viewpoint used for image-model registration. Such correspondences are used to create a coherent feature-correspondence mapping (similar to the dense correspondence in Shih et al's work [33]). The silhouette edges of O and P o are automatically retrieved using the tech- nique by Suzuki and Abe [34].…”
Section: Feature-correspondence Mappingmentioning
confidence: 99%